Grace of the Empire State : a novel - Tizzard, Gemma (Gallery Books, 2025)
"After the death of their father, it's up to Grace O'Connell and her twin brother Patrick to support their family as the Great Depression takes its toll on New York City. When Grace is laid off from her dancing gig and Patrick is injured at work on the construction of the Empire State Building, desperation leaves them only one solution: Grace must disguise herself as Patrick and take his place on the half-built skyscraper. She soon proves herself as capable as any man on the steel, and her affection for the loyal men around her--especially Italian immigrant Joe--grows by the day. But when a terrible accident happens high above the city and Grace is the only one capable of saving her stranded colleague, she must make a split-second decision to risk everything or live with her conscience forever. Set against the backdrop of a city at a crossroads, this electrifying story is full of heart and hope, family and friendship, and the sacrifices we make for those we love"--